Percutaneous kyphoplasty and vertebroplasty in children: A systematic review - Beaudelaire Romulus Assan; Mèhomè Wilfried Dossou; Wilfried Innocent Munkado Meuga; Yannelle Agbodjogbé; Raïssa Abibatou Yasmina Diaby; Joël Emmanuel N’guessan Brou; Laté Dzidoula Lawson; Nourou Dine Adeniran Bankolé (Interdisciplinary Neurosurgery)
Background: Currently, vertebral augmentation is primarily used to treat vertebral compression fractures in adults. However, an increasing literature reports its use in the paediatric population. Aim: To summarise the indications, technical aspects and results of paediatric percutaneous kyphoplasty and vertebroplasty. Methods: We performed an electronic search of PubMed/ Medline English literature on PKP and PVP without time limitation. Results: Seven studies (3 case reports and 4 case series) with a total of 21 patients and 46 vertebral augmentations were included. The procedure is mainly performed in adolescents with a mean age of 10.2 years (range 5–13, SD 2.9) and a sex ratio of 4.3. Indications can be divided into 4 groups (traumatic, malformative, tumour and osteoporotic). Balloon percutaneous kyphoplasty and vertebroplasty were the techniques used for thoracic and lumbar vertebrae, with posterior fixation in 57 % of cases. Polymethylmethacrylate was the only cement used and no leakage was reported. The mean operative time was 118 min (range 77–148, SD 14). Results were excellent in terms of pain reduction, neurological dysfunction and restoration of spinal alignment. Mortality was 19 %, exclusively due to malignant progression. Conclusion: This review provides evidence of the feasibility and efficacy of percutaneous kyphoplasty and vertebroplasty in children. No evidence of complications was found, suggesting that the technique is safe. Further studies involving larger patient groups would allow us to refine these aspects further.